Trust in Institutions, Social Solidarity, and the Perception of Social Cohesion in the Republic of Moldova in the Early Phase of the COVID-19 Pandemic - Negură Petru; Gașper Lucia; Potoroacă Mihai (Comparative Southeast European Studies, 2021)
Research shows that social cohesion is crucial to the promotion of public health and the response to pandemic disease. This paper discusses a few key aspects of social cohesion in Moldova in the early phase of the COVID-19 pandemic, namely trust in the government, social solidarity, and the perception of social cohesion. The article uses data from two sources: first from in-depth interviews carried out in May 2020 with 95 people of high status, and then from a nationally representative survey conducted in July 2020. We also compared the case of Moldova with those of other European countries regarding trust in institutions and success in combating the pandemic. The paper suggests that awareness of the COVID-19 pandemic was correlated with socioeconomic status, education, and by respondents’ trust in institutions. The interviewees participating in the qualitative research defined social cohesion as the observance of health rules and suggested that solidarity and social support were uneven during the crisis.